PENGARUH PIJAT BAYI TERHADAP MOTORIK KASAR PADA BAYI USIA 6 – 12 BULAN DI WILAYAH KERJA PUSKESMAS PULAU SAPI - Fetrie Olavianty; Agus Purnamasari; Teresia Suminta Rotua Situmorang (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2024)
One of the procedures that is often done on babies is baby massage. Baby massage is a treatment that involves giving a gentle touch to the baby's body, either structured or unstructured. Massage carried out periodically or routinely on babies' feet, stomach, chest, hands, back and stretching movements can improve gross motor development in babies their age. The aim of the research was to determine the effect of baby massage on the motor skills of babies aged 6 - 12 months in the Sapi Island Health Center Working Area. The type of research used is Quasi Experimental, One Group Pretest-posttest design. The population in this study were all babies aged 6 – 12 months who had had their baby's development checked at the UPTD Puskesmas Pulau Sapi in 2024, totaling 15 respondents. Univariate analysis in this research used the frequency distribution of baby age, frequency distribution of gender, frequency distribution of motor development before and after baby massage. Then bivariate analysis uses the Wicoxon Sign Rank Test and before carrying out this test it is necessary to carry out a Normality test on the gross motor variable. Normality test results show sig 0.000 < 0.05, which means the data is not normally distributed, which means the Wilcoxon Sign Rank Test can be continued. The results for the Wilcoxon Sign Rank Test were 0.000, there was an influence on gross motor development before and after giving massage to babies aged 6 - 12 months. So it can be done regularly to optimize the baby's gross motor development.